Genetic variation in the ABCG2 gene is associated with gout risk in the Chinese Han population. Issue 1 (January 2016) - Jiri, Mutu; Zhang, Le; Lan, Bing; He, Na; Feng, Tian; Liu, Kai; Jin, Tianbo; Kang, Longli
Abstract Gout is a common type of arthritis that is characterized by hyperuricemia, tophi, and joint inflammation. Current evidence suggests that heredity contributes to the progression of gout. Previous studies have shown that regulation of the ATP-binding cassette subfamily G member 2 (ABCG2 ) pathways plays a role in gout occurrence. To investigate and validate potential genetic associations with the risk of gout, we conducted a case–control study. We conducted 143 cases and 310 controls and genotyped seven single-nucleotide polymorphisms (SNPs) inABCG2 gene.ABCG2 SNP association analyses were performed using SPSS 17.0 Statistical Package, PLINK Software, HaploView software package, and SHEsis software platform. We identified that four susceptibility SNPs were potentially associated with occurrence of gout. Rs2622621 and rs3114018 inABCG2 can actually increase the risk of gout in log-additive model (rs2622621, odds ratio (OR) = 1.90, 95 % confidence interval (CI) 1.39–2.61, p  < 0.001; rs3114018, OR = 1.55, 95 % CI 1.13–2.13, p  = 0.006). We found that rs17731799G/T-G/G and rs3114020 T/C-T/T inABCG2 can actually increase the risk of gout in dominant model (rs17731799, OR = 1.67, 95 % CI 1.05–2.66, p  = 0.028; rs3114020, OR = 1.58, 95 % CI 1.00–2.51, p  = 0.048). TheABCG2 haplotype "GGCTCTC" (OR = 0.46, 95 % CI 0.28–0.75, p  = 0.0019) decreased the gout risk. Our results, combined with those from previous studies, suggest that genetic variation inABCG2 may influence gout susceptibility in the Han population.